Ab initio prediction of the electronic, magnetic and topological properties of Ln2O3 clusters. (26th May 2017) - Xia, Xiuli; Shao, Yuanzhi
Abstract: The structural, electronic and magnetic properties of the lanthanide oxide Ln2 O3 clusters, where Ln signifies lanthanides from La to Lu, have been calculated using spin-polarized density functional theory with the B3LYP hybrid functional. The intensities of ferromagnetic RKKY interaction are found comparable with that of antiferromagnetic superexchange interaction in Ce2 O3 / Pr2 O3 / Nd2 O3 / Gd2 O3 / Tb2 O3 / Tm2 O3 clusters, while the other Ln2 O3 clusters prefer ferromagnetic states to antiferromagnetic states in energy, except nonmagnetic La2 O3 and Lu2 O3 clusters. The theoretical spin magnetic moments, calculated three-dimensional spin density maps and dipole moments of Ln2 O3 clusters suggest that the induced polarizations of oxygen atoms in Sm2 O3, Eu2 O3 and Yb2 O3 clusters remarkably lead to the elongated Ln–O bond lengths in these clusters. The partial density of states of Ln2 O3 clusters reveals that Sm 3+ /Eu 3+ /Yb 3+ ions are distinctive from other Ln 3+ ions in that their Ln-4 f electrons are strongly hybrid with O-2 p electrons. The topological analysis of the electron density was also performed with quantum theory of atoms in molecules, which indicates the ionic Ln–O bonds have partial covalent characteristics.